Peningkatan kapasitas digital marketing melalui media sosial bagi UMKM keripik pisang di Tiris - Moh. Fadel; Irfan Maulana; Muhammad Koyyim (P3HKI - Universitas Muhammadiyah Parepare, 2024)
The banana chips MSME (Micro, Small, and Medium Enterprise) in Ranu Agung Village faces marketing challenges due to its reliance on conventional methods and limited digital capabilities. This community service initiative aimed to enhance the digital marketing capacity of MSME actors through rebranding training and social media optimization. The implementation involved initial field observation to assess partner needs, logo design training using Canva, social media utilization workshops focusing on Instagram and Facebook, and a one-month mentoring period. The results indicate significant improvement in participants' abilities to develop product visual identities, manage social media accounts, and independently produce promotional content. Additionally, digital engagement and product orders increased by 30% during training. These findings suggest that digital marketing strategies tailored to the specific needs of MSMEs can significantly impact their business development. The success of the program was further supported by effective collaboration between the implementation team and the MSME partner, as well as an adaptive approach to overcoming technical constraints.